BAB‐random‐C Monomer Sequence via Radical Terpolymerization of Limonene (A), Maleimide (B), and Methacrylate (C): Terpene Polymers with Randomly Distributed Periodic Sequences. Issue 7 (12th January 2017) - Ojika, Masataka; Satoh, Kotaro; Kamigaito, Masami
Abstract: A naturally abundant terpene, limonene (A), was radically polymerized with a maleimide derivative (B) and methacrylate (C) in a fluorinated alcohol to give terpolymers with unprecedented BAB‐random‐C sequences in which the BAB monomer sequence was randomly copolymerized with a C unit. In each binary system, limonene was hardly copolymerized with methacrylate while it was efficiently copolymerized with maleimide to result in a 1:2‐alternating BAB periodic sequence, in part due to the penultimate effects and hydrogen‐bonding interactions with fluoroalcohol. Methacrylate and maleimide were randomly copolymerized to give copolymers rich in methacrylate units with minimal amounts of maleimide–maleimide sequences. Their terpolymerization resulted in a BAB‐r‐C sequence as a consequence of the selective BAB polymerization between limonene and maleimide, the random copolymerization between methacrylate and maleimide, and the lack of copolymerization between limonene and methacrylate. Abstract : Lemon aid : One of the most naturally abundant terpenes, limonene (A), was radically copolymerized with phenylmaleimide (B) and methyl methacrylate (C) in a fluoroalcohol to result in terpolymers with unprecedented BAB‐ random ‐C sequences. This sequence is a consequence of selective BAB polymerization between A and B, random copolymerization between B and C, and almost no copolymerization between A and C.